"I'm almost opioid-a-phobic": family medicine residents' perceptions of enhancing opioid analgesic and agonist treatment training in a Canadian setting - Narayan, Shawna; Brath, Hana; Di Marco, Danielle; Maclure, Malcolm; McCracken, Rita; Klimas, Jan (Education for primary care, 2023)
PURPOSE: As deaths from the illicit drug poisoning crisis continue to rise in Canada, increasing the number of healthcare professionals qualified to effectively prescribe opioids could be beneficial. The willingness of family medicine residents to undertake structured training in prescribing opioids for Opioid Agonist Treatment (OAT) and pain management have not been well described. MATERIALS AND METHODS: Family medicine residents (n = 20) in British Columbia, Canada, were asked about their experience with and willingness to enrol in OAT training. Informed by the Consolidated Framework for Implementation Research, data were analysed thematically using NVivo software. RESULTS: Four themes were identified: (1) challenges to training implementation, (2) feelings and attitudes on prescribing practices, (3) helpful learning spaces and places of substance use training, and (4) recommendations for implementing training. Preparedness, exposure, and supportive learning environments for substance use education increased willingness to pursue OAT accreditation, while ineffective learning experiences, mixed feelings about opioid prescribing, and lack of protected time were the most common reasons for unwillingness. CONCLUSIONS: Protected time and a range of clinical experiences appear to facilitate residents' willingness to complete OAT and opioid training. Implementation strategies to enhance the uptake of OAT accreditation in family medicine residency must be prioritised.
Keywords: opioid agonist treatment; rodinné lékařství; opioidní analgetika; Practice Patterns, Physicians'; lidé; Kanada; family medicine; pain management; Canada; Substance-Related Disorders; Training; Analgesics, Opioid; opioids; lékařská praxe - způsoby provádění; poruchy spojené s užíváním psychoaktivních látek; Humans; Family Practice